2019
DOI: 10.1155/2019/3412952
|View full text |Cite|
|
Sign up to set email alerts
|

Double-Blind, Randomized, Three-Armed, Placebo-Controlled, Clinical Investigation to Evaluate the Benefit and Tolerability of Two Dosages of IQP-AE-103 in Reducing Body Weight in Overweight and Moderately Obese Subjects

Abstract: Objective. This study was performed to determine the efficacy and tolerability/safety of IQP-AE-103 on body weight reduction in overweight to moderately obese adults. Methods. A double-blind, randomized, placebo-controlled trial involved one hundred and eight subjects (BMI between 25 and 35 kg/m2) that were randomly assigned to either the low-dose or the high-dose IQP-AE-103 group, or the placebo group. Following a 2-week run-in period, subjects received two capsules of investigational product after three dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 47 publications
0
13
0
1
Order By: Relevance
“…However, phytochemical analysis has shown that okra was safe up to the dose of 2 g/kg in rats treating with aqueous and methanolic seed extract of okra for 1 week (Doreddula et al, 2014). Moreover, obese patients who take two capsules of okra pods (330 mg of A.esculentus) three times in day for 12 weeks have shown no adverse effect of okra in the performed clinical trial (Uebelhack et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, phytochemical analysis has shown that okra was safe up to the dose of 2 g/kg in rats treating with aqueous and methanolic seed extract of okra for 1 week (Doreddula et al, 2014). Moreover, obese patients who take two capsules of okra pods (330 mg of A.esculentus) three times in day for 12 weeks have shown no adverse effect of okra in the performed clinical trial (Uebelhack et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A beneficial effect of IQP-AE-103 on the lipid metabolism was also demonstrated in the subgroup of subjects with baseline total cholesterol levels above 6.2 mmol/L. The study indicated that IQP-AE-103 could be an effective and safe weight loss intervention; the trial was registered with NCT03058367 [ 140 ]. However, currently, a trial to evaluate the glycemic evaluation of okra seed noodles is currently active, although not recruiting; see ( Identifier: NCT03990844).…”
Section: Safety and Efficacymentioning
confidence: 99%
“…IQP-AE-103 is a combination of dehydrated powder of okra pods [ Abelmoschus esculentus (L.) Moench] and inulin, a heterogeneous mixture of fructose polymers extracted from chicory roots ( 14 , 15 ). This study demonstrated significant weight loss, a reduction in feelings of hunger, and a decrease in BMI, body fat mass, and waist and hip circumference as compared with the placebo ( 13 ). Much of the noted benefits were thought to be the result of the dietary fat binding by IQP-AE-103 and the physicochemical swelling and gel-forming properties of okra pods, which have been shown to induce satiety in vivo ( 13 ).…”
Section: Introductionmentioning
confidence: 71%
“…In a previously published, double-blind, placebo-controlled, 12-week trial, overweight and moderately obese subjects on a hypocaloric diet were treated with IQP-AE-103 ( 13 ). IQP-AE-103 is a combination of dehydrated powder of okra pods [ Abelmoschus esculentus (L.) Moench] and inulin, a heterogeneous mixture of fructose polymers extracted from chicory roots ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%